Metabolic and Proteomic Responses to Salinity in Synthetic Nitrifying Communities of Nitrosomonas spp. and Nitrobacter spp. - Ilgrande, Chiara; Leroy, Baptiste; Wattiez, Ruddy; Vlaeminck, Siegfried Elias; Boon, Nico; Clauwaert, Peter (Frontiers in Microbiology, 2018)
Nitrification is typically a two-stage microbial process and is key to wastewater treatment and nutrient recovery from waste streams. Changes in salinity represent a major stress factor, that can trigger response mechanisms impacting the activity and the physiology of the bacteria. Despite its pivotal biotechnological role, little information is available on the specific response of nitrifying bacteria to varying levels of salinity. In this study, synthetic communities of ammonia oxidizing bacteria (AOB Nitrosomonas europaea and/or Nitrosomonas ureae) and nitrite oxidizing bacteria (NOB Nitrobacter winogradskyi and/or Nitrobacter vulgaris) were tested at 5, 10 and 30 mS cm-1 by addition of sodium chloride to the mineral medium (0, 40 and 200 mM NaCl, respectively). Ammonia oxidation activity was less affected by salinity than nitrite oxidation. AOB, on their own or in combination with NOB, showed no significant difference in ammonia oxidation rates among the three conditions. However, Nb winogradskyi improved the absolute ammonia oxidation rate of both Ns europaea and Ns ureae. Nitrobacter winogradskyi’s nitrite oxidation decreased to 42% residual activity upon exposure to 30 mS cm-1, showing a similar behavior also when tested with Nitrosomonas spp. The nitrite oxidation rate of Nb vulgaris as a single species was not affected by the addition of sodium chloride up to 30 mS cm-1, however its activity was completely inhibited when combined with Nitrosomonas spp. in presence of ammonia. The proteomic analysis of a co-culture of Nitrosomonas europaea and Nitrobacter winogradskyi revealed the production of osmolytes, regulation of cell permeability and oxidative stress response in Ns europaea and oxidative stress response in Nb winogradskyi as a result of increasing the salt concentration from 5 to 30 mS cm-1. A specific metabolic response observed in Ns europaea suggests a role of the carbon metabolism in the production of reducing power, possibly to meet the energy demands of the stress response mechanisms induced by salinity. For the first time, metabolic modifications and response mechanisms caused by the exposure to salinity were described, serving as a tool towards controllability and predictability of nitrifying system exposed to salt fluctuations.